Penerapan Layanan Opencourseware Open Library Telkom University sebagai Media Pembelajaran Gratis - Maliha, Ilma; Anwar, Rully Khairul; Rodiah, Saleha (Universitas Sebelas Maret Library, 2023)
The research entitled Implementation of Open Courseware Services in Telkom University Open Library as a Free Learning Media aims to obtain a clear picture of the steps for implementing Open Courseware Open Library Services. This research is motivated by the motivation of Open Library to provide information and provide easy access to information by providing free learning in the form of learning video content for the general public through the Open Library open courseware service. In this study using a case study approach with qualitative research methods equipped with data collection techniques through observation, interviews and documentation. The Open Library opencourseware service was used as the object of research and 4 informants in this study were used as research subjects. Based on the analysis of research data and drawing conclusions, the results of this study indicate that the steps for implementing the open courseware Open Library service consist of planning, collecting references, entering data, setting topics, processing or production, controlling material, storing data, reporting editing results, review of learning content, storage and posting of learning materials. In implementing the open courseware Open Library service, there are influencing elements consisting of the communicator, message, context, media, and recipient.